Let C be the curve (where x takes all real values).The tangent at A except (0,0) meets the curve again at B.If the gradient at B is k times the gradient at A,then k is equal to
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let A ( x 0 , x 0 3 ) for x 0 > 0 with the tangent line y − x 0 3 = ( 3 x 0 2 ) ( x − x 0 ) ⇒ y = ( 3 x 0 2 ) x − 2 x 0 3 . If this tangent line is to insect the curve again at point B, then let B ( − k x 0 , − k 3 x 0 3 ) for k > 0 and substitute it into the tangent line:
− k 3 x 0 3 = ( 3 x 0 2 ) ( − k x 0 ) − 2 x 0 3 ⇒ 0 = k 3 − 3 k − 2 = ( k − 2 ) ( k + 1 ) 2 ⇒ k = − 1 , 2 .
After discarding the negative root, the gradient at point B computes to:
d x d y ∣ x = − 2 x 0 = 3 ( − 2 x 0 ) 2 = 1 2 x 0 2
which is 4x the gradient at point A.